Mitochondrial Dysfunction in Repeat Expansion Diseases - Alberto Giménez-Bejarano; Eva Alegre-Cortés; Sokhna M. S. Yakhine-Diop; Patricia Gómez-Suaga; José M. Fuentes (Antioxidants, 2023)
Repeat expansion diseases are a group of neuromuscular and neurodegenerative disorders characterized by expansions of several successive repeated DNA sequences. Currently, more than 50 repeat expansion diseases have been described. These disorders involve diverse pathogenic mechanisms, including loss-of-function mechanisms, toxicity associated with repeat RNA, or repeat-associated non-ATG (RAN) products, resulting in impairments of cellular processes and damaged organelles. Mitochondria, double membrane organelles, play a crucial role in cell energy production, metabolic processes, calcium regulation, redox balance, and apoptosis regulation. Its dysfunction has been implicated in the pathogenesis of repeat expansion diseases. In this review, we provide an overview of the signaling pathways or proteins involved in mitochondrial functioning described in these disorders. The focus of this review will be on the analysis of published data related to three representative repeat expansion diseases: Huntington’s disease, C9orf72-frontotemporal dementia/amyotrophic lateral sclerosis, and myotonic dystrophy type 1. We will discuss the common effects observed in all three repeat expansion disorders and their differences. Additionally, we will address the current gaps in knowledge and propose possible new lines of research. Importantly, this group of disorders exhibit alterations in mitochondrial dynamics and biogenesis, with specific proteins involved in these processes having been identified. Understanding the underlying mechanisms of mitochondrial alterations in these disorders can potentially lead to the development of neuroprotective strategies.